Pengaruh Edukasi Gizi Melalui Media Sosial terhadap Pengetahuan Gizi dan Pemilihan Menu di Aplikasi Pesan Antar Makanan: The Effect of Nutrition Education Through Social Media on Nutritional Knowledge and Menu Selection in Food Delivery Application - Rahmanita Femyliati; Al Mukhlas Fikri; Eka Andriani (Amerta Nutrition, 2023)
Background: Adolescents tend to use online food delivery service applications rather than going to food stalls or restaurants to buy food, but most of the food and drinks offered contain high levels of fat, sodium, and sugar but are low in other nutrients. Currently, WhatsApp ranks first in the social media category with the most active users, with teenagers being one of the users. Previous studies have not yet analyzed behavior change and the effectiveness of each medium in the same study. Therefore, the authors are interested in conducting research by providing nutrition education interventions through WhatsApp through digital posters, audio, and video. Objectives: Analyzed the effect of nutrition education through social media on nutritional knowledge and menu selection in food delivery applications. Methods: This research design was quasi-experimental. This research was conducted in Bekasi in 2022, with the research sample being teenagers using food delivery applications and WhatsApp. The number of samples in this study was 111, divided into three groups: audio, poster, and video. Knowledge improvement was assessed by the results of pre-test and post-test questionnaires, while changes in menu selection were seen from the results of 2x24 hour Food Recall. Nutrition education was carried out four times with a frequency of 1 time a week through the WhatsApp group. The effect of nutrition education on knowledge and menu selection was analyzed using the Wilcoxon test, paired t-test, and Kruskal Wallis. Results: There was an effect of knowledge of balanced nutrition, so there was a significant difference in nutritional knowledge (p<0.05) in the subjects of the entire intervention group after being given the intervention. Likewise, the menu selection in the food delivery application experienced a positive change after the intervention (p<0.05). The subject began to choose nutrient-dense menus in the food delivery application. However, there was no difference in effectiveness between educational media (p>0.05). Conclusions: There is an effect of nutrition education using audio, poster, and video on menu selection in food delivery applications.